X-ray diffraction and thermodynamic characteristics for tellurite of the composition Li2CeTeO5 - Rustembekov, K. T.; Bekturganova, A. Zh. (SPRINGER, 2017)
Tellurite of the composition Li2CeTeO5 is synthesized by solid-phase method from cerium(IV) and tellurium(IV) oxides and lithium carbonate. The type of syngony, the unit cell parameters, and the compound’s X-ray and pycnometry densities are determined via X-ray diffraction analysis. The isobaric heat capacity of lithium–cerium tellurite is studied by means of dynamic calorimetry in the temperature range of 298.15–673 K; the results serve as the basis for deriving C p ° ~ f(T) dependency equations and determining the compound’s thermodynamic functions. λ-shaped anomalous effects, due probably to Type II phase transitions, are found on the C p ° ~ f(T) dependence.
Keywords: lithium–cerium tellurite; X-ray diffraction analysis; heat capacity; thermodynamic functions